Determination of Slope Stability using (UAV) Unmanned Aerial Vehicle - Subramaniam, Tarvin Raj; Suhaimi, Nurul Nazhatul Aqmanisha; Paizol, Afzal; Mat Nor, Ahmad Hakimi (Multidisciplinary Applied Research and Innovation, 2022)
In this modern era, conventional methods of slope monitoring is not recommendable due to high risk. For example, maintenance employees may be required to climb to the top of a hill to take photographs in order to check slope stability. As a result, the goal of this study is to investigate an alternative approach.which is through the usage of UAV (Unmanned Aerial Vehicle) aircraft to monitor slope stability conditions. The goal of this project was to use UAVs to monitor slope conditions whether it safe or not. The following goals were set in order to attain that goal by generating orthomosaic images, Digital Terrain Model (DTM) and Digital Surface Model (DSM) captures by using Pix4d mapper software.Moreover, analyzing drainage system images taken by UAV and analyzing slope watershed using global mapper software. This study was conducted at the hillside area behind Pagoh Residential College (3). Pre-flight planning and preparation, data retrieval utilising UAV aircraft, image processing using Pix4dmapper software, and slope evaluation using Global Mapper software are all included in the process. Thereafter, slope conditions can be determined based on slope drainage monitoring.With photos acquired from the UAV, the condition of the slope surface, such as cracks in the slope structure and excessive plant growth on the slope drainage, can be seen in this research.In addition, the gradient, elevation and flow of water on the surface can be known. Thus, the usage of UAV aircraft in slope monitoring and inspection was successful and the purpose of this study was achieved because these devices showed excellent propensity and those softwares to support our research were able to be used efficiently with our supervisor’s guidance.Last but not least,study research were able to be fulfilled and slope conditions were able to be monitored even though many obstacles appeared during this pandemic era.